Good and Evil Actions : A Journey through Saint Thomas Aquinas - Jensen, Steven J., 1964- (Book collections on Project MUSE., 2010)
"In Good and Evil Actions, Steven J. Jensen tackles the Thomistic debate surrounding the inherent good and evil of human actions. With exceptional clarity, he identifies the essential issues, resolves conflicting views, and reveals the truth as conveyed by Aquinas."--Jacket